Analysis and Perspective on Heat Pump for Industrial Steam Generation. Issue 5 (6th May 2021) - Yan, Hongzhi; Wang, Ruzhu; Du, Shuai; Hu, Bin; Xu, Zhenyuan
Abstract : Sustainable Manufacturing In article number 2000108, Ruzhu Wang and co‐workers study possible steam generation paths based on heat pump and propose a novel path to turn water into high‐temperature steam by an air‐source heat pump with a temperature lift over 100 °C, which could be a sustainable solution for industrial heating decarbonization. The "AIR for STEAM" in the picture illustrates the concept that utilizing heat from ambient air for steam generation, where the heat pump "O" in the middle of "for" is the key. The dial in the middle of the heat pump symbolizes the temperature scale. It shows that the air source heat pump can abstract heat from the ambient surroundings to heat water up to 120–150 °C high temperature steam. The water tap on the right side is connected to the heat pump through the pipeline, which symbolizes the water input and is used to generate steam. The red fluid below symbolizes high‐temperature and high‐pressure steam, which is sent to the corresponding factory for industrial uses.